2016
DOI: 10.1111/ans.13653
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of surgical approach for the management of renal cell carcinoma: a population‐based study from New South Wales

Abstract: The unintended decrease in PN associated with increased use of laparoscopic RN had reversed by 2009. Hospital case load predicts the use of PN and laparoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
22
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 20 publications
4
22
0
Order By: Relevance
“…We identified a progressive increase in the utilization of NSS in Australia over the past 15 years, consistent with smaller state‐based studies . While this could be due to a greater proportion of cases performed as PN in the private sector, as noted by Patel et al ., this trend is in keeping with multiple international studies . Specifically, a significant increase from 17% to 38% was observed between 2002 and 2014 in a Veterans Health cohort, which also described greatest and least uptake in younger and older patients, respectively, much like that observed in this study.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We identified a progressive increase in the utilization of NSS in Australia over the past 15 years, consistent with smaller state‐based studies . While this could be due to a greater proportion of cases performed as PN in the private sector, as noted by Patel et al ., this trend is in keeping with multiple international studies . Specifically, a significant increase from 17% to 38% was observed between 2002 and 2014 in a Veterans Health cohort, which also described greatest and least uptake in younger and older patients, respectively, much like that observed in this study.…”
Section: Discussionsupporting
confidence: 90%
“…We identified a progressive increase in the utilization of NSS in Australia over the past 15 years, consistent with smaller state‐based studies . While this could be due to a greater proportion of cases performed as PN in the private sector, as noted by Patel et al ., this trend is in keeping with multiple international studies .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…As we do not have data regarding the surgical management of small RCC tumours prior to 2009, we do not know whether use of NSS to treat T1a tumours was increasing during the 2000s, suggesting the increase we found between 2009 and 2013 was simply a continuation of this trend; however, Patel et al. showed that use of NSS for all RCC tumours was relatively stable between 2005 and 2008 at 20% in the Australian state of New South Wales. While not conclusive, this could suggest the increase in NSS found in the present study was in response to the publication of the international guidelines recommending use of NSS for small renal tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Over the period of the present study, the proportion of patients treated in low‐volume hospitals decreased, while the proportion treated in middle‐volume hospitals increased. As several studies, including ours in univariable analyses, have shown a positive association between higher hospital renal cancer volumes and likelihood of NSS , this change is encouraging; however, unlike a recent European study that found no change in the use of NSS for T1 tumours in low‐volume hospitals , the present study found an increasing trend towards NSS for small renal tumours even in low‐volume hospitals. As our study used slightly different definitions for low‐volume hospitals, we repeated our analyses using the same volume definitions as those used in the European study , and found the same pattern of results as those presented in this paper.…”
Section: Discussionmentioning
confidence: 99%